2003
DOI: 10.1002/eji.200323571
|View full text |Cite
|
Sign up to set email alerts
|

Immune evasion of Borrelia burgdorferi: mapping of a complement‐inhibitor factor H‐binding site of BbCRASP‐3, a novel member of the Erp protein family

Abstract: The causative agents of Lyme disease, Borrelia burgdorferi s.s., B. garinii, and B. afzelii, differ in their susceptibility to complement‐mediated lysis. This phenomenon apparently depends on the expression of proteins termed complement regulator‐acquiring surface proteins (CRASP) and their binding to the inhibitory plasma proteins factor H and FHL‐1. To characterize these bacterial proteins in more detail we have now isolated from a B. burgdorferi expression library a novel factor H‐binding protein. In accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
138
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 43 publications
11
138
0
Order By: Relevance
“…Orthologous genes have been identified in all other Lyme disease spirochete genospecies, although it is not yet clear whether or not the encoded proteins bind factor H and FHL-1 (Rogers and Marconi, 2007, and our unpublished results). BbCRASP-3, -4, and -5 lipoproteins all belong to the Erp paralog family, and their respective genes are named erpP, erpC, and erpA, or, collectively, ospE (Stevenson et al, 1996Casjens et al, 2000;Hellwage et al, 2001;Alitalo et al, 2002Alitalo et al, ,2004Kraiczy et al, 2003Kraiczy et al, ,2004aMetts et al, 2003). erp loci are all located on borrelial prophages which replicate as circular episomes known as cp32s .…”
Section: Bbcrasp-encoding Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthologous genes have been identified in all other Lyme disease spirochete genospecies, although it is not yet clear whether or not the encoded proteins bind factor H and FHL-1 (Rogers and Marconi, 2007, and our unpublished results). BbCRASP-3, -4, and -5 lipoproteins all belong to the Erp paralog family, and their respective genes are named erpP, erpC, and erpA, or, collectively, ospE (Stevenson et al, 1996Casjens et al, 2000;Hellwage et al, 2001;Alitalo et al, 2002Alitalo et al, ,2004Kraiczy et al, 2003Kraiczy et al, ,2004aMetts et al, 2003). erp loci are all located on borrelial prophages which replicate as circular episomes known as cp32s .…”
Section: Bbcrasp-encoding Genesmentioning
confidence: 99%
“…produces several different outer surface proteins collectively termed CRASPs (complement regulator-acquiring surface proteins). These lipoproteins share affinities for the host fluid phase negative regulators of complement factor H and/or FHL-1 (factor H-like protein 1) (Hellwage et al, 2001;Kraiczy et al, 2001Kraiczy et al, , 2003Kraiczy et al, , 2004aKraiczy et al, , 2004bAlitalo et al, 2002Alitalo et al, , 2005Stevenson et al, 2002;McDowell et al, 2003;Hartmann et al, 2006;Kraiczy and Würzner, 2006;Herzberger et al, 2007). Those two host proteins promote breakdown of C3b and inactivation of the alternative pathway C3 convertase (Janeway et al, 1999;Kraiczy and Würzner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies indicated that moderate or fully complement-resistant B. burgdorferi and Borrelia afzelii strains, but not complementsensitive Borrelia garinii strains, express up to five factor H-and FHL-1-binding surface molecules termed complement regulator-acquiring surface proteins (CRASPs) (13,34,35). According to their ability to differentially bind factor H and FHL-1, CRASPs of complement-resistant B. burgdorferi (BbCRASPs) and B. afzelii (BaCRASPs) strains are divided into three groups: factor H-and FHL-1-binding proteins (BbCRASP-1, BaCRASP-1, BbCRASP-2, and BaCRASP-2), FHL-1-binding proteins (BaCRASP-3), and factor H-binding proteins (BbCRASP-3-5, BaCRASP-4, and BaCRASP-5) (34,36).…”
mentioning
confidence: 99%
“…According to their ability to differentially bind factor H and FHL-1, CRASPs of complement-resistant B. burgdorferi (BbCRASPs) and B. afzelii (BaCRASPs) strains are divided into three groups: factor H-and FHL-1-binding proteins (BbCRASP-1, BaCRASP-1, BbCRASP-2, and BaCRASP-2), FHL-1-binding proteins (BaCRASP-3), and factor H-binding proteins (BbCRASP-3-5, BaCRASP-4, and BaCRASP-5) (34,36). More recently, BbCRASP-3 has been characterized on a molecular level and identified as a novel member of the polymorphic Erp (OspE/F-related proteins) family (35). BbCRASP-3 and multiple homologous Erp proteins expressed by virulent B. burgdorferi strains were shown to bind factor H (12,(37)(38)(39)(40).…”
mentioning
confidence: 99%
“…Streptococcus pyogenes for example has been shown to use the C5a and C3 peptidase ScpA [21], M protein mediated C4BP binding [22] and the C5b-C9 inhibitory protein SIC [23] to circumvent complement. Gram negative Borrelia burgdorferi inhibits complement via multiple FH binding proteins [24] and enterohemorrhagic Escherichia coli can cleave C1-INH and thus enhance its complement inhibitory function [25]. For S. suis complement evasion has not been intensively studied and so far only the sialic acid containing capsule of certain serotypes and factor H binding molecules have been described as complement evasion factors [26,27].…”
Section: Discussionmentioning
confidence: 99%